Too few cooks spoil the broth: division of labour and directed production - Ratto, Marisa; Schnedler, Wendelin (Discussion paper series, 2008)
How can a manager influence workers' activity while knowing little about it? This paper examines a situation where production requires several tasks, and the manager wants to direct production to achieve a preferred allocation of effort across tasks. However, the effort that is required for each task cannot be observed, and the production result is the only indicator of worker activity. This paper illustrates that in this situation, the manager cannot implement the preferred allocation with a single worker. On the other hand, the manager is able to implement the preferred allocation by inducing a game among several workers. Gains to workers from collusion may be eliminated by an ability-dependent, but potentially inefficient, task assignment. These findings provide a new explanation for the division of labor, and bureaucratic features such as "over"-specialization and "wrong" task allocation.